Empowering Women via Social Safety Nets and Service Delivery (Journal of Governance and Development (JGD), 2014)
Social safety Nets (SSNs) are the form of government intervention to assist the â€œneedyâ€ groups including the single mothers. SSNs should be established as a mechanism that can be used to alleviate poverty, especially among single mothers. However, the barrier that restricts SSNs as mechanism to improve the quality of life for single mothers is a failure of service delivery functions. The single mothers can be empowered through good delivery system of SSNs because it can support their social development. Basically, SSNs is used as short term supporting system to generate independent nature of life and consciousness among women (single mothers). Thus this study aims to identify the delivery of SSNs services or assistance to single mothers that they received and the problems they faced. Face-to-face interviews were conducted with four selected single mothers in different districts in Perlis. The result indicates that they are in need of the SSNs to support their single motherhood. While SSNs are available to the single mothers, it is hindered either by inefficient delivery system and/or their personal constraints.